2011
DOI: 10.1007/s11250-011-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental yeast culture and physiological factors on colostrum and milk composition of Pelibuey ewes

Abstract: The effects of supplemental yeast culture, litter size, stage and number of lactation on milk composition were studied in Pelibuey ewes. Twenty ewes were randomly assigned to one of two dietary treatments. Ten control ewes grazed on guinea grass (Panicum maximum) and were supplemented with concentrate. A further ten ewes received the same diet with 14 g/head/day of yeast culture (Saccharomyces cerevisiae). Colostrum was collected within 24 h after parturition, and subsequently, milk samples were collected at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…No SC effect was seen on colostrum composition over time in our study, in accordance with Macedo et al (79) , who observed no effect of a culture of S. cerevisiae on ewes' colostrum nutritional composition and yield. Contrarily, a cocktail of Bacillus licheniformis and B. subtilis (BioPlus 2B) supplementation increased daily milk yield, fat and protein contents and decreased lamb mortality (mainly due to diarrhoea) from 13⋅1 to 7⋅8 % (80) .…”
Section: Effect Of Live Yeast Supplementation In Late Gestation On Co...supporting
confidence: 93%
“…No SC effect was seen on colostrum composition over time in our study, in accordance with Macedo et al (79) , who observed no effect of a culture of S. cerevisiae on ewes' colostrum nutritional composition and yield. Contrarily, a cocktail of Bacillus licheniformis and B. subtilis (BioPlus 2B) supplementation increased daily milk yield, fat and protein contents and decreased lamb mortality (mainly due to diarrhoea) from 13⋅1 to 7⋅8 % (80) .…”
Section: Effect Of Live Yeast Supplementation In Late Gestation On Co...supporting
confidence: 93%
“…No SC effect was seen on colostrum composition over time in our study, in accordance with Macedo et al, 77 who observed no effect of a culture of S. cerevisiae on ewes' colostrum nutritional composition and yield. Contrarily, a cocktail of Bacillus licheniformis and B. subtilis (BioPlus 2B) supplementation increased daily milk yield, fat and protein contents and decreased lamb mortality (mainly due to diarrhea) from 13.1% to 7.8 % 78 .…”
Section: The Effect Of Live Yeast Supplementation In Late Gestation On Colostrum and Hypothesis On Mechanisms Involved In Colostrum Qualisupporting
confidence: 92%
“…The number of lambs born from the one ewe influences the quality of milk -higher milk fat percentages were noted in ewes rearing twins than in those rearing one lamb (Snowder and Glimp, 1991). Also, tropical conditions can influence percentage of milk total solids: the more lambs are reared by the ewe the more total solids are present in the milk (Macedo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%